RANCANGAN APLIKASI PENCARIAN TOKO HANDPHONE MURAH DAN TERDEKAT DI KOTA BATAM BERBASIS ANDROID - HARTONO, EDY; Fauzi, Rahmat (LPPM Universitas Putera Batam, 2021)
The rapid development of technology in the field of information and communication, especially Android-based smartphone devices, resulted in observations from researchers, namely the emergence of difficulties for prospective buyers from outside the city of Batam in finding cheap and nearby cellphone shops that were the background for the design of this system. The system is expected to make it easier for people to find cheap and closest mobile phone shops using the Haversine and GPS methods on Android phones quickly and efficiently so that people are interested in buying. The results of making a search application for the nearest mobile phone shop provide information about cellphone shops such as maps, shop contacts, and shop descriptions. From making the application, it can also make it easier for potential cellphone buyers to find the cheapest and closest cellphone shops using the Haversine Formula algorithm to solve this problem, by taking the shortest distance data between the user's location and the location of the cellphone shop. Therefore, this application makes it easier for potential buyers to find cellphone shops.